Studi Kasus Terjadinya Auto Switch yang Tidak Diinginkan pada Pompa Sistem Minyak Pelumas untuk Main Engine - Kurniawan, Ratna Dwi; Wirawan, Yuris Bahadur (Marine Science and Technology Journal, 2022)
The Oil lubricating system is a support system for the main engine for ship main propulsion. The main engine runs for 24 hours non-stop and all the time while sailing so that the support system must function every time. To ensure that the function runs normally, the components in the support system are provided in redundancy or more than one, if one component performance a decrease in function it will automatically be replaced by a second component, this time is used for the first component to carry out maintenance. The problem that occurs in this case is that the panel will automatically activate the 1st pump, and if it is moved to the 2nd pump, the pump will run but only for a minute then it will auto switch to pump 1st again, after observing and several times testing and analyzing the system The root of the problem can be found, which is not in the electrical system but in the mechanical components. The methods used in this mass resolution are case studies and literature reviews. The conclusion obtained is that a system cannot stand alone, be it mechanical or electrical, it is closely related to other components. This article was compiled with the intention of being able to be used by practitioners and students related to problems in the lubricant system in analyzing problems that occur.